Endometriosis is associated with a lowered cumulative live birth rate: A retrospective matched cohort study including 3071 in vitro fertilization cycles. (June 2022) - Zhou, Linyan; Wang, Linlin; Geng, Qiang; Zhang, Hongzhan; Xu, Shiru; Diao, Lianghui; Zeng, Yong; Mo, Meilan; Li, Longfei
Abstract: Endometriosis, defined as the presence of endometrial tissues outside the uterus, affects approximately 10% of women of reproductive age. Assisted reproductive technology (ART) is considered the most effective technique to treat infertility in women, although the impact of endometriosis on ART outcomes remains ambiguous. In this study, 433 patients with endometriosis and 1299 infertile patients with tubal factors receiving in vitro fertilization (IVF) treatment were retrospectively enrolled to determine whether a history of endometriosis affects pregnancy outcomes. Patients with endometriosis had markedly fewer retrievable oocytes, a lower oocyte maturity rate, and decreased numbers of available and high-quality embryos (all p  < 0.001) compared to those with tuber factors. The rates of clinical pregnancy and live birth in the endometriosis group were lower in the frozen-thawed embryo transfer cycles ( p  = 0.028 and p  = 0.008, respectively), and a decreased cumulative live birth rate (CLBR) ( p  = 0.001) was observed. Logistic regression analysis revealed a negative association between endometriosis and CLBR ( p  = 0.002). The number of macrophages in the follicular fluid (FF) of patients with ovarian endometriosis was significantly higher than that of patients without ovarian endometriosis ( p  < 0.001). The levels of interleukin (IL)− 1α, IL-1β, tumor necrosis factor-α, IL-6, IL-13, and IL-10 in FF were also elevated in the endometrioma group than in the control group ( p  < 0.05). These results indicate that endometriosis is negatively associated with CLBR in IVF, which may be caused by the follicular immune microenvironment that affects the development and fertilization of oocytes. Highlights: Endometriosis adversely affects pregnancy outcomes of assisted reproduction. Endometriosis was associated with lower cumulative birth rate. Endometriosis was associated with poor oocyte or embryo outcomes. Endometriosis was associated with increased macrophages in follicular fluid. Imbalance of anti- and pro-inflammatory cytokines was observed in endometriosis.